Helicobacter pylori infection process: from the molecular world to clinical treatment - Yi, Meijing; Chen, Silan; Yi, Xinying; Zhang, Fan; Zhou, Xuan; Zeng, Meiyan; Song, Houpan (Frontiers in Microbiology, 2025)
Helicobacter pylori is a gram-negative microaerophilic microorganism intricately associated with chronic gastrointestinal disorders and gastric cancer. H. pylori can cause various upper digestive tract diseases, including chronic gastritis, peptic ulcer, gastroesophageal reflux disease, and gastric cancer. The bacterium exhibits a variety of pathogenic mechanisms, including colonization, the expression of virulence factors, and the development of drug resistance. This article presents a comprehensive review of H. pylori pathogenesis, emphasizing recent research advancements concerning the cytotoxin-associated gene A, vacuolating cytotoxin, outer membrane proteins, and other virulence factors. Additionally, it examines the molecular mechanisms underlying drug resistance and evaluates the efficacy of conventional therapeutic approaches. Recently, researchers have attempted novel therapeutic regimens, including probiotics and Chinese medicine-assisted therapies, to enhance therapeutic effects. This article aimed to offer an overview of the academic community’s comprehension of H. pylori infection and to highlight the current treatment options.